??????? ???????? ?? ????? ???? ????? ???? ???? - Khairul Fuadi (AL MA'ANY, 2024)
The novel "Zaynab" by Muhammad Husein Haikal is one of the first novels in modern Arabic literature. The novel makes Zaynab the main character in the story, the author is very skilled at playing with the reader's emotions through the storyline he builds. To further research, the researcher uses library research methods and qualitative analysis in this study, this study discusses the author's biography, synopsis, and various intrinsic elements in the novel such as ideas, plot, language style, characters, and messages. The results of the study show that this novel criticizes patriarchal traditions, especially forced marriage, and highlights the importance of individual freedom and gender equality. This novel uses a descriptive, simple, and realistic language style to describe rural life in Egypt and the deep emotions of its characters. The message of this novel is the need for fair social change and empathy for disadvantaged individuals. This study contributes to understanding the transformation of Arabic literature from classical to modern through Haikal's work. ????? ????? "????" ?????? ???? ???? ???? ?? ????? ???????? ?? ????? ?????? ??????. ??????? ???? ???? ??????? ???????? ?? ?????? ??????? ???? ???? ?? ??????? ?????? ?????? ?? ???? ????? ???? ??????. ????? ?? ?????? ?????? ?????? ????? ????? ??????? ???????? ?????? ?? ??? ?????? ?????? ??? ????? ???? ?????? ?????? ???????? ???????? ???????? ?? ??????? ??? ??????? ??????? ?????? ????? ????????? ????????. ????? ????? ????? ?? ??? ??????? ????? ???????? ???????? ????? ?????? ??????? ????? ????? ??? ????? ?????? ??????? ????????? ??? ???????. ?????? ??? ??????? ??????? ?????? ?????? ?????? ???????? ???? ?????? ??????? ?? ??? ???????? ??????? ?????????. ????? ??? ??????? ?? ?????? ??? ??????? ????????? ?????? ???????? ?? ??????? ????? ???. ????? ??? ????? ?? ??? ???? ????? ?????? ?? ????????? ??? ?????? ?? ???? ????? ????